UPAYA MENINGKATKAN KUALITAS PENYERAPAN ANGGARAN SULAWESI SELATAN TAHUN 2023 - Rahmanto, Dedi (Unitri Press, 2024)
Purpose: This study aims to analyze the quality of budget implementation by work units partnering with KPPN Makassar I in the first semester of 2023, focusing on factors affecting the low level of budget absorption. The method used was a survey utilizing questionnaires, which were distributed to 80 respondents from work units in Makassar City, Maros, and Pangkep. The questionnaire was designed to collect data on aspects of Budget Revision, Disbursement, Work Execution, Administration, Human Resources (HR), and Compliance. Data analysis was performed by evaluating responses to these aspects. The survey results indicate that the quality of budget implementation is at a moderate level, with problems ranging from 40% to 60%. The two main issues identified are Budget Revision and Work Execution. In the context of Budget Revision, the Automatic Adjustment process and frequent revisions of the POK (Work Output Planning) are the primary challenges. Meanwhile, in Work Execution, the biggest challenges are the hindered procurement process and difficulties in carrying out operational spending proportionally. The study's conclusion emphasizes the importance of improving coordination among relevant parties and enhancing planning quality to address these challenges and encouraging efficiency and effectiveness in future budget implementation.